우울 및 불안장애 환자에서 리질리언스와 감사 성향의 관련성 - 민정아; 이원희; 정영은; 홍현미; 채정호; Min, Jung-Ah; Lee, Won Hee; Jung, Young-Eun; Hong, Hyeonmi; Chae, Jeong-Ho (Anxiety and mood, 2022)
Objective : The levels of resilience and gratitude were examined in psychiatric patients with depression and/or anxiety disorders and compared to those of the general population. In addition, we analyzed the associations of positive affect, negative affect, depressive and anxiety symptoms, and gratitude on resilience in this patient population. Methods : The participants included a general population sample (n=155) and psychiatric outpatients with depression and/or anxiety disorders (n=108). All participants completed self-report questionnaires, which included demographic variables, the Connor-Davidson Resilience Scale (CD-RISC), the Gratitude Questionnaire-Six-Item Form (GQ-6), the Positive Affect Negative Affect Scale (PANAS), and the Hospital Anxiety and Depression Scale (HADS). Results : The CD-RISC and GQ-6 scores of patients with depression and/or anxiety disorders were significantly lower than those of the general population. In the patient population, hierarchical regression analysis showed that gratitude was significantly associated with resilience while controlling for a range of demographic and clinical variables. Conclusion : Patients with depression and/or anxiety disorder generally had lower resilience and gratitude. Moreover, our findings showed that gratitude could influence the levels of resilience in patients with depression and/or anxiety disorders.